2020
DOI: 10.1177/0272431620978531
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Early to Late Adolescents’ Attachment Figures in a Multicohort Six-Wave Study: Person- and Variable-Oriented Approaches

Abstract: Although Bowlby proposed that adolescence is a major developmental period to transfer their attachment figures from parents to other people, no comprehensive longitudinal study on attachment transfer from early to late adolescence exists. This study employed 215 early to late adolescents between ages 11 and 18 years ([Formula: see text] = 14.02, SD = 2.05 at Wave 1), using a six-wave 2-year longitudinal design with four different cohorts: 5th, 7th, 9th, and 11th grades. Both person- and variable-oriented analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This reassignment pattern fits with previous research ( Umemura et al, 2017 ; Wrzus et al, 2017 ), showing that partners gradually take over from friends as attachment figures, as a romantic relationship develops further, and particularly after two years. It has been demonstrated clearly that, although the impact of a romantic relationship starts to modify attachment networks even during the first few months ( Fagundes and Schindler, 2012 ), roughly two years are needed to develop a full attachment bond with the partner ( Hazan and Zeifman, 1994 ; Umemura et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This reassignment pattern fits with previous research ( Umemura et al, 2017 ; Wrzus et al, 2017 ), showing that partners gradually take over from friends as attachment figures, as a romantic relationship develops further, and particularly after two years. It has been demonstrated clearly that, although the impact of a romantic relationship starts to modify attachment networks even during the first few months ( Fagundes and Schindler, 2012 ), roughly two years are needed to develop a full attachment bond with the partner ( Hazan and Zeifman, 1994 ; Umemura et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, individuals do experience shifts in key attachment figures across developmental phases, with the parentchild attachment relationship diminishing in importance over time. For example, in a multicohort longitudinal study (6 waves) by Umemura et al (2021), it was found that starting from early adolescence, children begin to rely less on parents and main caregivers as key attachment figures, with a "transfer" in attachment figures from parents to friends being likely to occur at about age 13. The transfer also seems to be largely irreversible, where a greater proportion of late adolescents (around age 18) relied on their friends or romantic partners as attachment figures compared to parents.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, friends can restore feelings of comfort and security following threats, and can confer confidence to explore new environments. Supporting these ideas, developmental research shows that by middle childhood, children increasingly turn to their friends for emotional support, by late adolescence, peers are often preferred over parents as sources of comfort, and in adulthood, friends remain a source of comfort and security [53,63,64,69,70].…”
Section: Do the Individuals Involved In The Social Disconnection Inte...mentioning
confidence: 99%